Re-evaluation of lunation of the activity of somantibacterial drugs against clinical isolates of Escherichia coli in al- najaf al- ashref governorate - Nashtar, Saad B.; Sheeh, Adel . H (AL-Kindy College Medical Journal, 2010)
ackground: Escherichia coli is one of the most important bacterial pathogen that can cause several disease to human being . In our study we try to investigate the sensitivity resistance pattern of Escherichia coli against three antibiotics ( Amikacin, Nalidixic acid and Cephalexin). Methods: For this purpose we collected 51 clinical isolates of Escherichia coli from stool and urine of outpatient and inpatient patients from different wards of AL-SADER Teaching Hospital in AL-NAJAF AL-ASHRAf, IRAQ, and tested by culture and sensitivity test . Results: The results appeared that Amikacin show the highest percentage of sensitivity ( 66.66 % ) , while Cephalexin show the lowest percentage of sensitivity ( 6.34 % ) . Conclusions: we conclude that Amikacin is the most sensitive antibacterial drug for Escherichia Coli as compared with Nalidixic acid and Cephalexin, while Cephalexin is the most resistant antibacterial drug for Escherichia Coli as compared with Amikacin and Nalidixic acid.